1031. Impact of Meningitis-Encephalitis PCR Panel Testing on Antimicrobial Use in Patients with Suspected Meningoencephalitis. (15th December 2022) - Rodriguez, Julieta; Ahuja, Monica; Moore, Franklin; Marie, Peter St; Lindsey, Kristy; Paez, Armando
Abstract: Background: Meningoencephalitis continues to be a source of morbidity and mortality in the US despite vaccine development. Traditional culture-based diagnosis is time-consuming and less sensitive than molecular methods. Meningitis-encephalitis PCR panel (MEP) testing of CSF allows for rapid detection of 14 culprit microorganisms. Methods: A retrospective cohort study was performed at University of Massachusetts Chan Medical School-Baystate in Springfield, MA between May 15, 2015 and May 14, 2017 on encounters among 163 individuals ranging in age from neonates to geriatric patients before and after MEP introduction for clinical practice. One cohort reflected pre-MEP availability and relied on culture and gram stain while another cohort had the MEP available and gram stain/culture. The primary outcomes were (1) MEP effect on antimicrobial de-escalation and (2) total antimicrobial days defined as sum of days on antimicrobial therapy counting each antimicrobial agent separately. Secondary outcomes were (1) length of hospital stay, (2) rate of adverse events associated with antimicrobial use, and (3) determination if adult or pediatric age interplayed with interpretation of MEP results. Results: Fifty-two percent of the population was 18 years-old or younger. The most common organisms identified were parechovirus and enterovirus. There were 26 positive MEP panels and nine encounters did not de-escalate antimicrobials. Seven of the nine did not de-escalate because there was concern for sepsis or blood culture was positive. The remaining two either started or continued acyclovir for a positive MEP of HSV-2 or VZV. When the MEP resulted positive for bacteria, antimicrobials were modified. Mean time antimicrobial use was less when MEP was available (3.1 vs. 4.8 days) and length of hospitalization was similar (6.1 vs. 6.9 days). Adverse events were minimal in both groups. Identified Organisms Microorganisms identified by MEP overall, pediatric, and adult. Total Antimicrobial Days and Length of Stay by Cohort Pre-MEP and MEP available cohort distribution on total antimicrobial days and length of stay in pediatric and adult populations. Conclusion: The data did identify difference in management with interpretation of the MEP for pediatrics (≤ 18 y/o) when compared to adults. Fever in a neonate, or severely ill child led to a 48 hour blood culture rule out prior to any change in antibiotics. Overall, our study showed association of MEP use with early antimicrobial de-escalation that can potentially lead to decreased length of stay and savings in healthcare costs. Disclosures: All Authors : No reported disclosures.